New records of Woodiphora biroi (Brues, 1907) and a possible sibling species of Woodiphora parvula Schmitz, 1927 (Diptera: Phoridae) from Peninsular Malaysia - Raja Muhammad Zuha Raja Kamal Bashah,; Disney, R. Henry L. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Scuttle flies (Diptera: Phoridae) can be found in various habitats with important roles in the ecosystem as parasites, predators and decomposers. Currently there are more than 270 genera of Phoridae worldwide and Woodiphora has been recognized as one of the most prevalent group in the Australasian and Oriental region. Previous decomposition studies using animal carcasses indicated there were more species likely to be discovered from Malaysia. In this paper, the first occurrence of Woodiphora biroi (Brues, 1907) from Peninsular Malaysia and a possible sibling species complex of Woodiphora parvula Schmitz, 1927 which could not be named until linked to its male were reported. The latter has different abdominal tergites and furca from previously described species. Samples were collected from baited-flight traps placed at selected locations in Bangi, Selangor, as prescribed herein. This report extends our knowledge on the distribution and bionomics of Woodiphora from this region.